Beatrice Rose Waldinger papers - Waldinger, Beatrice Rose.
Correspondence and writings including articles, partial drafts of books, and poetry pertaining to the Freud family, Waldinger's immigration to the U.S. in 1938, her interest in psychoanalysis, and her analysis with Paul Federn. Correspondents include family members, especially her husband poet Ernst Waldinger and cousin Anna Freud, and others including Hermann Broch, K. R. Eissler, Paul Federn, and Thornton Wilder.
Writer and niece of Sigmund Freud. Born 1896; died 1969.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Broch, Hermann, -- 1886-1951 -- Correspondence; Eissler, K. R. -- 1908-1999 -- Correspondence; Federn, Paul; Federn, Paul -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Waldinger, Ernst, -- 1896- -- Correspondence; Wilder, Thornton, -- 1897-1975 -- Correspondence; Freud family; Emigration and immigration; Psychoanalysis; Authors